Explaining trajectories of adolescent drunkenness, drug use, and criminality: A latent transition analysis with socio-ecological covariates. (March 2020) - Turner, Russell; Daneback, Kristian; Skårner, Anette
Highlights: There are different trajectories in adolescent substance use and criminal behaviour. Trajectories are largely stable in early to mid-adolescence. The different trajectories are likely to have different causal mechanisms. Family cohesion and criminal peers was linked to an entrenched group. Implications for theory, policy and practice are discussed. Abstract: Background: Although there are diverse trajectories in adolescent substance use and criminality, it is less clear why some adolescents follow one pathway and not another. In this study, we examine how different domains in a young person's life, such as temperament, peer, and family factors, are linked to different trajectories and whether some domains are more strongly associated with specific patterns of these behaviours. Methods: Data comes from the Longitudinal Research on Development in Adolescence (LoRDIA) study in Sweden. Adolescents were surveyed at baseline (n = 755, age 13, grade 7) and followed up at grades 8 and 9. Latent transition analysis and multinomial logistic regression were conducted. Results: Four distinct statuses were found, showing heterogeneity in adolescent substance use and criminal behaviours. These statuses were however highly stable. Individual, peer and family domains were all relevant in distinguishing between the statuses. A key finding is that the relative importance of these domains differed between statuses, suggesting differential effects of the domains on the different trajectories. The pre-teen family environment, as well as criminal peers, was most strongly associated with a more entrenched group. This was not the case for a 'Dabblers' group, where novelty-seeking was weakly linked. For the 'Occasional Law Breakers', criminal peers was more strongly associated. Conclusions: Our results suggest that substance use and criminality in early to mid-adolescence is more diverse than current theories allow. Moreover, the different trajectories in these behaviours are likely to have different causal mechanisms, which has important implications for theory, policy and practice.